Breaking Symmetry Relaxes Structural and Magnetic Restraints, Suppressing QTM in Enantiopure Butterfly Fe2Dy2 SMMs. Issue 61 (21st October 2021) - Baniodeh, Amer; Wagner, Danny; Peng, Yan; Kaemmerer, Hagen; Leblanc, Nicolas; Bräse, Stefan; Naubron, Jean‐Valére; Anson, Christopher E.; Powell, Annie K.
Abstract: The Fe2 Dy2 butterfly systems can show single molecule magnet (SMM) behaviour, the nature of which depends on details of the electronic structure, as previously demonstrated for the [Fe2 Dy2 (μ3 ‐OH)2 (Me‐teaH)2 (O2 CPh)6 ] compound, where the [N, N‐bis‐(2‐hydroxyethyl)‐amino]‐2‐propanol (Me‐teaH3 ) ligand is usually used in its racemic form. Here, we describe the consequences for the SMM properties by using enantiopure versions of this ligand and present the first homochiral 3d/4 f SMM, which could only be obtained for the S enantiomer of the ligand for [Fe2 Dy2 (μ3 ‐OH)2 (Me‐teaH)2 (O2 CPh)6 ] since the R enantiomer underwent significant racemisation. To investigate this further, we prepared the [Fe2 Dy2 (μ3 ‐OH)2 (Me‐teaH)2 (O2 CPh)4 (NO3 )2 ] version, which could be obtained as the RS ‐, R ‐ and S ‐compounds. Remarkably, the enantiopure versions show enhanced slow relaxation of magnetisation. The use of the enantiomerically pure ligand suppresses QTM, leading to the conclusion that use of enantiopure ligands is a "gamechanger" by breaking the cluster symmetry and altering the intimate details of the coordination cluster's molecular structure. Abstract : These 2 coordination clusters are similar but different both in the fine details of their structures as well as their magnetic behaviour. [Fe2 Dy2 (μ3 ‐OH)2 (Me‐teaH)2 (O2 CPh)6 ], which normally forms with the racemic version of Me‐teaH3 by using enantiopure ligand, allows access to the S ‐version, but for the R ‐version there is significant racemisation. Surprisingly, by using the synthesis of [Fe2 Dy2 (μ3 ‐OH)2 (Me‐teaH)2 (O2 CPh)4 (NO3 )2 ] both enantiopure R ‐ and S ‐compounds were obtained. In both cases breaking the symmetry of the parent compounds leads to enhanced SMM behaviour.